Stretchable Optomechanical Fiber Sensors for Pressure Determination in Compressive Medical Textiles. Issue 15 (29th May 2018) - Sandt, Joseph D.; Moudio, Marie; Clark, J. Kenji; Hardin, James; Argenti, Christian; Carty, Matthew; Lewis, Jennifer A.; Kolle, Mathias
Abstract: Medical textiles are widely used to exert pressure on human tissues during treatment of post‐surgical hematoma, burn‐related wounds, chronic venous ulceration, and other maladies. However, the inability to dynamically sense and adjust the applied pressure often leads to suboptimal pressure application, prolonging treatment or resulting in poor patient outcomes. Here, a simple strategy for measuring sub‐bandage pressure by integrating stretchable optomechanical fibers into elastic bandages is demonstrated. Specifically, these fibers possess an elastomeric photonic multilayer cladding that surrounds an extruded stretchable core filament. They can sustain repetitive strains of over 100%, and respond to deformation with a predictable and reversible color variation. Integrated into elastic textiles, which apply pressure as a function of their strain, these fibers can provide instantaneous and localized pressure feedback. These colorimetric fiber sensors are well suited for medical textiles, athletic apparel, and other smart wearable technologies, especially when repetitive, large deformations are required. Abstract : Color‐tunable photonic fibers are used as pressure sensors to quantify sub‐bandage pressure in compression therapy via readily perceivable color variations. Relying on a photonic fiber design that combines intrinsic material elasticity with controlled nano and microscale structuring, this approach enables accurate adjustment and monitoring of sub‐bandage pressure, which is critical to improving treatment outcomes.